Intrinsically Noncombustible Thermosets from Sulfur-Containing Epoxy Resin and Benzoxazines: Evaluation of Thermal and Mechanical Properties - Ya Lyu; Haibo Fan; Liliang Qiu (Advances in Polymer Technology)
Benzoxazine (BZ)-epoxy copolymers exhibit favorable mechanical properties, but their thermal and flame-retardant characteristics are impaired at high epoxy fractions. Here, we report a new type of sulfur-containing epoxy resin (EPS), which we synthesized using 4,4’-thiobisphenol (TBP) instead of bisphenol A (BA) and then blended with three sulfur-containing BZs (TBP-a, TBP-fa, and TBP-tma). The polymerization behavior of the resins was analyzed using Fourier transform infrared spectroscopy and differential scanning calorimetry for determining the optimal curing procedure. This analysis revealed that the oxazine and epoxy rings undergo ring-opening and cross-linking reactions at the same time and that double-substituted structures originating from the furan and thiophene rings appeared during the curing process. Thermogravimetric analysis showed that the addition of EPS increased the initial decomposition temperature by hindering the formation of double-substituted structures. The char yield at 800°C decreased owing to the unstable C–O–C–C–O groups derived from the ring-opening of EPS. To prepare the self-extinguishing copolymers with a char yield of 24%, a smaller quantity of BZ was needed for the EPS-based blends than for the BA-based ones. The heat release capacities—measured using micro-combustion calorimetry—of all copolymers except TBP-a/EPS were less than 300 J/g·K, demonstrating that the presence of thioether bonds and double-substituted structures resulted in excellent flame retardancy. The TBP-fa/EPS copolymer also exhibited excellent flame retardancy in cone calorimeter measurement. Finally, the glass transition temperature of the TBP-fa/EPS copolymer at a ratio of 5 : 5 (w/w) reached as high as 289°C. A TBP-fa/EPS copolymer with an epoxy content of 70% had nearly the same storage modulus (2,206 MPa) at 50°C as poly(BA-a) and thus similar mechanical properties. In summary, BZ-epoxy copolymers prepared from sulfur-containing epoxy combine the advantages of the constituent components and extend their areas of application.